Cenobamate for the treatment of focal epilepsies. (11th December 2020) - Strzelczyk, Adam; Mann, Catrin; Willems, Laurent M.; Rosenow, Felix; Bauer, Sebastian
ABSTRACT: Introduction: Antiseizure drugs (ASDs) play a central and crucial role in the treatment of epilepsy patients because the majority require anticonvulsant treatment for an extended period of time. Due to the fact that 30% of patients are refractory to medical treatment, new therapeutic options are necessary. Cenobamate is the latest approved antiepileptic drug in focal epilepsy, and its mode of action is thought to be mediated by blocking voltage-gated sodium channels and interaction with the GABAergic system. Areas covered: This article reviews animal studies, pharmacokinetics, pharmacodynamics, and the phase 1 to 3 trials and open-label extension data on cenobamate. Expert opinion: Cenobamate has the potential to perform as an important ASD because trial data are indicative of remarkable responder and seizure freedom rates so far not seen with other ASDs. Cenobamate demonstrated significant efficacy at a dosage between 100 and 400 mg per day. The side-effect profile of this drug is comparable to other ASDs and is mainly CNS related; in particular, somnolence, dizziness, headache, diplopia, and nystagmus. However, slow titration is mandatory to decrease the risk of drug rash with eosinophilia and systemic symptoms (DRESS) that was observed in several patients with fast uptitration schemes.